Manejos de inverno associado ao pastejo animal: efeito na cultura da soja - Carvalho, Rodrigo Damasceno (My University, 2024)
Different managements in land use have important influences on physical, chemical and biological qualities. The objective of this work was to evaluate different winter managements associated or not with grazing, in the productivity of the soybean crop in succession. The experiment was carried out in a commercial crop in the municipality of São Francisco de Paula - RS. Conducted as a factorial 2 (with and without soil cover in winter) x 2 (with and without trampling + harrowing) in a plot design with five replications each. Four plots were allocated for evaluation with different management practices, one plot without green cover, but with the effect of trampling (T1), a plot with the use of cover crops combined with crop-livestock integration (T2), a plot with the presence of green cover, without the presence of animals (T3) and a fallow plot without cover plant and without the presence of animals (T4). In plots (T1) and (T2) light harrowing was carried out after the end of the grazing period and before planting soybeans. In the summer harvest (2022/2023), the soybean crop was implemented and the average plant height, number of pods, grains per pod and crop productivity were evaluated. The different soil managements contributed with significant interactions regarding plant height, number of pods per plant and number of pods per plant. However, we conclude that in the short term these factors do not interfere with the productivity of the crop. [resumo fornecido pelo autor]
Diferentes manejos no uso do solo detêm importantes influências sobre as qualidades físicas, químicas e biológicas. O objetivo desse trabalho foi avaliar diferentes manejos de inverno associado ou não ao pastejo, na produtividade da cultura da soja em sucessão. O experimento foi realizado em uma lavoura comercial no município de São Francisco de Paula - RS. Conduzido como fatorial 2 (com e sem cobertura de solo no inverno) x 2 (com e sem pisoteio + gradagem) em delineamento em parcelões com cinco repetições cada. Foram destinadas quatro parcelas para avaliação com diferentes manejos, sendo uma parcela sem cobertura verde, mas com efeito do pisoteio (T1), uma parcela com uso de plantas de cobertura aliada a integração lavoura-pecuária (T2), uma parcela com a presença de cobertura verde, sem a presença de animais (T3) e uma parcela de pousio sem planta de cobertura e sem a presença de animais (T4). Nas parcelas (T1) e (T2) foi realizada uma gradagem leve após o final do período de pastejo e antes da implantação da soja. Na safra de verão (2022/2023), foi implantada a cultura da soja e avaliado a altura média das plantas, número de legumes, grãos por legume e a produtividade da cultura. Os diferentes manejos do solo contribuíram com interações significativas quanto a altura das plantas, o número de vagens por planta e o número de legumes por plantas. Porém, concluímos que a curto prazo esses fatores não interferem sobre a produtividade da cultura. [resumo fornecido pelo autor]
Keywords: Agronomia; Soja - Cultivo; Produtividade; Solos - Composição